1987
DOI: 10.1016/0014-4827(87)90101-7
|View full text |Cite
|
Sign up to set email alerts
|

Phorbol ester binding and protein kinase C activity in normal and transformed human keratinocytes

Abstract: Normal keratinocytes, SV40-transformed keratinocytes (SVKi4), and various squamous carcinoma cell (XC) lines have been used as an in vitro model system to study the properties of phorbol ester receptor and protein kinase C expression during keratinocyte differentiation. The cell lines used exhibit a decreasing capacity to differentiate in the order of keratinocytes -SVK,,>SCC-12F2>SCC-15>SCC-4; moreover, all cell lines respond to a low external Ca*+ concentration by a decreased capacity to differentiate. Norma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
11
0

Year Published

1989
1989
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 26 publications
(10 reference statements)
0
11
0
Order By: Relevance
“…induced translocation of PKC from the cytosol to the particulate fraction in a manner analogous to that reported with PMAstimulation [Snoek et al, 1987]. Thus, the similarity between the effects of mechanical strain and chemical agonists on PKC signaling would suggest some similarities in distal transduction events.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…induced translocation of PKC from the cytosol to the particulate fraction in a manner analogous to that reported with PMAstimulation [Snoek et al, 1987]. Thus, the similarity between the effects of mechanical strain and chemical agonists on PKC signaling would suggest some similarities in distal transduction events.…”
Section: Discussionmentioning
confidence: 70%
“…Although the demonstration of strain-induced activation of PKC activity and translocation in keratinocytes is novel, the characteristics of the response have some similarity to previously described stimulation of keratinocytes by chemical agonists such as phorbol esters. First, the magnitude of strain-induced PKC activation in keratinocytes (184% maximal increase) was slightly less than the 200% increase previously reported for stimulation of PKC activity by PMA [Snoek et al, 1987]. Second, the onset of straininduced activation of PKC (5 min) is comparable to that previously described for PMA (5 min, Reynolds et al, 1994].…”
Section: Discussionmentioning
confidence: 77%
“…COULOMB et al (3) showed that increased serum concentration in the culture medium inhibits uptake of benzo[a]pyrene and benzo[e]pyrene by hamster embryo fibroblasts. Similarly, phorbol ester binding to cells is affected by such factors as stage of cell maturation, Ca' * content of the medium, and cell phospholipid composition (4)(5)(6). Other studies have shown that retinoic acid and NNN may decrease and increase, respectively, the binding of phorbol esters to oral epithelial celis and these correlated with changes in cell lipids (7,8).…”
mentioning
confidence: 99%
“…The discovery by Nishizuka and colleagues that the phorbol ester receptor was identical to PKC (Castagna et al, 1982) strongly suggested that the direct activation of PKC by phorbol esters was responsible for some of the observed biological responses to these tumor promoters. Subsequent studies have demonstrated phorbol ester receptors in murine (Dunn and Blumberg, 1983;Solanki and Slaga, 1982;Delclos et al, 1980;Ashendell et al, 1983) and human (Chi& andKuroki, 1983;Greenebaumet al, 1983;Snoek et al, 1987) keratinocytes. In addition, Dunn et al (1985) have correlated differences in the binding affinities of the phorbol receptors to the state of murine keratinocyte differentiation, suggesting that the phorbol re-ceptoriPKC is involved in the control of keratinocyte differentiation.…”
mentioning
confidence: 98%